2021
DOI: 10.4103/jfmpc.jfmpc_1775_20
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality and the need of mechanical ventilation in confirmed COVID-19 patients presenting to the emergency department in North India

Abstract: Background and Objectives: As the number of COVID-19 cases keeps on rising, a better awareness of the nature and severity of the disease will aid in clinical decision-making and management. Hence, this study was conducted to find the predictors of mortality and the need for mechanical ventilation in COVID-19 patients. Methods: This was a single centre, prospective observational study conducted in a tertiary care centre in north India. We included patients with influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It can be explained by higher chances of progression to multiple organ dysfunction syndrome because of these comorbidities, which necessitated ventilator requirements in these patients. [ 19 20 21 22 ] Yang et al .,[ 16 ] in their study on 200 patients with COVID-19, found a mortality rate in the ICU as 51.7%. Agarwal et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be explained by higher chances of progression to multiple organ dysfunction syndrome because of these comorbidities, which necessitated ventilator requirements in these patients. [ 19 20 21 22 ] Yang et al .,[ 16 ] in their study on 200 patients with COVID-19, found a mortality rate in the ICU as 51.7%. Agarwal et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] observed COVID-positive subject's death rate of 28.4% during the study of 281 SARI patients. Suresh et al .,[ 21 ] in their study on 116 COVID-19 patients, concluded that lower SpO 2 and Glasgow Coma Scale (GCS) were the main parameters that showed a significant association with mortality and the requirement for mechanical ventilation. Similarly, we also observed 34.1% of mortality in COVID-19 positive patients with SARI.…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer levels have been found to be consistently elevated in severe COVID-19 disease. 17 Comorbidities like diabetes are associated with adverse disease outcomes. RBS values at admission and HBA1C values are hence found to be directly associated with adverse disease outcomes 18 19 20…”
Section: Resultsmentioning
confidence: 99%